Median frequencies of prolonged ventricular fibrillation treated by V-A ECMO correspond to a return of spontaneous circulation rate - Havranek, Stepan; Belohlavek, Jan; Mlcek, Mikulas; Huptych, Michal; Boucek, Tomas; Svoboda, Tomas; Fichtl, Jaromir; Hrachovina, Matej; Linhart, Ales; Kittnar, Otomar (The International journal of artificial organs, 2014)
BACKGROUND: The aim of our study was to analyze, in a pig model of prolonged ventricular fibrillation (VF) treated by veno-arterial extracorporeal membrane oxygenation (ECMO), the time dependent changes of VF wavelet frequency obtained from intracardial signals and its relations to return of spontaneous circulation (ROSC). METHODS: 11 female pigs (50.3 ± 3.4 kg) under general anesthesia had undergone 15 min of VF with ECMO flow of 5 to 10 ml/kg per min simulating "untreated" VF followed by continued VF with full ECMO flow of 100 ml/kg per min. The median frequency (MF) of VF from right ventricular apex, coronary perfusion pressure, myocardial oxygen metabolism and resuscitability were determined. RESULTS: Median (interquartile range) of MF of fibrillatory wavelets in minute 15 of low ECMO flow [9.7 Hz (8.3; 10.1)] was not significantly changed in comparison to minute 1 [10.5 Hz (9.8; 12.4)], p = 0.12. Five minutes after full ECMO initiation MF increased [11.6 Hz (10.6; 13.5)], p = 0.04 (compared to minute 15 of VF) and did not deteriorate during the rest of ECMO treatment. Out of all subjects, three animals did not reach ROSC. Those subjects demonstrated deeper decrease of MF at the VF minute 15 as compared to others [-2.4 Hz (-2.5; -2.3) vs. -0.6 Hz (-1.6; -0.1)] and continuously significantly higher increase in MF on full ECMO support [4.3 Hz (2.9; 5.6) vs. 1.1 Hz (0.6; 1.6)] with p = 0.05 for both observations, respectively. CONCLUSIONS: The veno-arterial ECMO reperfusion influences MF of VF wavelet obtained from right ventricular apex. The course of changes in wavelet frequency corresponds to a presence of later ROSC.
Keywords: fibrilace komor; obnova funkce; Extracorporeal Membrane Oxygenation; Swine; Ventricular Fibrillation; Arterial Pressure; Female; Animals; arteriální tlak; ženské pohlaví; kardiopulmonální resuscitace; Disease Models, Animal; mimotělní membránová oxygenace; Cardiopulmonary Resuscitation; prasata; Recovery of Function; zvířata; modely nemocí na zvířatech